A geographical study of some factors that affect the location of deer farms in New Zealand : a thesis in partial fulfilment of the requirements for the degree of Master in Arts (Geography) at Massey Universit - Mawson, Ian Darcy (Massey University, 1978)
This study of the rapidly-expanding industry of deer farming does not claim to be an economic treatise on the commercial viability of farming deer, nor does it claim to be a practical manual for prospective and established deer farmers. It is, however, a document designed and written to help the farmers of deer understand themselves, and their infant industry, a little more fully, and to help other interested persons gain an insight into the development of the exciting new enterprise of farming deer. The underlying theme of the study is that the present distribution of deer farms throughout New Zealant after some eight years of development within the industry, is explainable. Such explanations are expressed in terms of the past and present cultural attitudes within New Zealand to deer, the resultant legislation and official actions taken, the major modes of diffusion of both the underlying notion involved and the successful, practical methods that have evolved, the characteristics of the deer farming operation itself as well as of the people involved in it, and the relative productivity of the land employed for the farming of deer, particularly in view of man's changing knowledge of deer. Regional variations in the distribution of deer farms, and in other related phenomena, are examined, and possible explanations for these are sought. Trends that have evolved within the industry up to the present time are examined, particularly in the light of more recently-gained scientific and empirical knowledge on both productivity and profitability. The future of the industry is then viewed with reference to these trends and to marketing outlets.
Keywords: Deer farming; New Zealand deer farming